Hubungan Antara Sense Of Humor Dengan Stres PadaMahasiswa Fakultas Psikologi UniversitasMuhammadiyah Surakarta - Herman, Setyaningrum Silviana, Drs. Zahrotul uyun, M. Si, Psi (2017)
Students have the responsibility to complete their studies, many of the obstacles that will be the pressure for the individual is stress. One of the factors that affect stress is the sense of humor. Where sense of humor is very useful for students to avoid the pressure that appears in him. The purpose of this study was to determine the relationship between the sense of humor with stress on the students of Psychology Faculty of Muhammadiyah University of Surakarta. The method used is quantitative method. The subjects used were psychology faculty students of 120 students. Sampling technique used is quota sampling technique. Measuring tool used is a scale of sense of humor and stress scale. The hypothesis used in this research is "There is a negative relationship between the sense of humor with stress on the students in the faculty of psychology", the method of analysis using product moment correlation technique with the help of SPSS (Stable Product Service Solution) 15.0 for windows program. The results obtained r value of -0.410; P = 0.000 (p <0.01), which indicates there is a very significant negative relationship between the sense of humor with stress on psychology faculty students of muhammadiyah university Surakarta. Which means the higher sense of humor then the student's stress level is low, and vice versa if the sense of humor is low then the student's stress level is high. Sense of humor has an empirical rate (RE) 87.79 and a hypothetical average (RH) of 72.5, and the category of sense of humor is high. Stress has an empirical mean (RE) 57.28 and a hypothetical average (RH) of 62.5, the category of stress is moderate. Effective contribution from the variable of sense of humor to stress on student is 16,81% and there are still 83,19% other factors that influence stress.